Acute myocardial infarction following inhaled treprostinil initiation - Bilal Alqam; Sarah Medrek (Respiratory Medicine Case Reports)
An 81-year-old man with a history of interstitial lung disease attributed to idiopathic pulmonary fibrosis, severe aortic stenosis, and stable coronary artery disease was started on inhaled treprostinil for pulmonary hypertension associated with interstitial lung disease to optimize hemodynamics prior to the valve replacement procedure. However, two days after starting this treatment, the patient presented with an inferior-posterior ST elevation myocardial infarction. Urgent coronary angiography revealed a 95 % proximal right coronary artery stenosis, successfully treated with percutaneous coronary intervention and drug-eluting stent placement. This case raises a question of whether there could be a potential association between inhaled treprostinil initiation and acute myocardial infarction in patients with underlying coronary artery disease. With the documented stability of the patient's coronary artery disease prior to medication initiation, it is plausible to question whether treprostinil may have played a role in plaque destabilization.